Identifying effective factors to alleviate postnatal distress and coronavirus anxiety in mothers of hospitalized preterm neonates - Borghei Narjes Sadat; Mehrbakhsh Zahra; Torklalebaq Fatemeh (BMC, 2023)
Abstract Background Given the critical importance of mental health in mothers of preterm neonates during the postpartum period for Population Youth Programs, our research aims to ascertain the correlation between postnatal distress and corona-induced anxiety in women who have hospitalized preterm neonates. Methods This descriptive-analytical study was conducted with a sample of 275 mothers of preterm neonates, were hospitalized in Gorgan city in 2020. Data collection was facilitated through the Corona Anxiety (CA) and Postnatal Distress Measured Scale (PDM). For data analysis, Spearman's correlation and univariate and multiple linear regression were employed. Results The average age of the participating mothers was 28.61 ± 6.173 years, and the average gestational age of the neonates was 32.8 ± 2.89 weeks. The study found a significant, positive correlation between CA and PDM. Controlling for other variables through multiple regression analysis, the factors that significantly influenced PDM were employment status (β = 3.88, p < 0.01), education level (β = 1.96, p = 0.032), and gestational age (β=-0.60, p < 0.001). Furthermore, number of living children (β=-4.77, p = 0.01), education (β=-2.37, p = 0.01), and gestational age (β=-0.91, p < 0.001) were the factors that were significantly associated with CA scores. Conclusions The correlation between CA and PDM suggests that preterm neonate's mothers experienced increased anxiety during the pandemic. Considering the factors influencing these anxieties, targeted programs should be developed to enhance the mental health of these mothers in future pandemics. The finding that women with more children experienced less CA could serve as evidence of the positive impact of having children on the mental health of women with premature infants during a pandemic.